Penggunaan Buzzer pada Modul GPS Teltonika FMB910 sebagai Indikator Kecepatan di PT Lacak Cipta Aktual - Aldi Bragi Muslim; Mohammad Fatkhurrokhman (International Forum of Researchers and Lecturers, 2026)
The development of transportation technology encourages companies to improve vehicle monitoring systems to be more effective and measurable, particularly in addressing speeding violations that can increase accident risks and reduce operational efficiency. This study aims to analyze the implementation and effectiveness of using a buzzer integrated with the Teltonika FMB910 GPS module as a vehicle speed warning indicator at PT. Lacak Cipta Aktual. This research employs a qualitative descriptive method with a case study approach, where data were collected through observation, interviews, and documentation during a one-month industrial internship and analyzed using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results show that the system is capable of detecting overspeed conditions and automatically activating the buzzer when the vehicle speed exceeds the predefined threshold of 80 km/h. Based on logbook data, the system achieved a success rate of 93.9% in responding to overspeed conditions. The use of a buzzer is proven effective in providing immediate warnings to drivers, thereby improving driver awareness and speed control. However, the system still has limitations, particularly its dependence on GPS signal stability and vehicle electrical conditions. Overall, this study demonstrates that the integration of GPS and a buzzer provides a simple, effective, and cost-efficient solution to enhance driving safety and fleet management efficiency.